Determining the Cost of Welded Joints - Donnelly, J.A. (Engineering Journal, 1968)
Relative cost factors are presented which relate the cost of fillet and groove welds of common sizes to the cost of a single pass ¼-in. fillet weld having an assigned cost factor of 1.00. Knowing the actual local cost of a ¼-in. fillet weld for various conditions, the relative cost factors presented may be used to determine the actual cost of welds of various kinds and sizes. The actual costs of fillet and groove welds are obviously best determined from rather precise time studies, wherein the value of all variables may be determined. Many of the variables are different for each fabricating shop. These weld cost variables include joint design, weld process, welding position, operating factor (arctime vs. total time), fit-up, local costs for material, labor, power, etc.